JAG1, MEF2C and BDNF polymorphisms associated with bone mineral density in women from Northern México - Sandra Marlen González-Peña; Eduardo Campos-Góngora; Hilda Guadalupe Ávila-Rodríguez; Erik Ramírez-López; Rafael Velázquez-Cruz; Zacarías Jiménez-Salas (Biomédica, 2018)
Introduction: Osteoporosis is characterized by a low bone mineral density. Genetic composition is one of the most influential factors in determining bone mineral density (BMD). There are few studies on genes associated with BMD in the Mexican population. Objective: To investigate the association of eight single nucleotide polymorphisms (SNP) of JAG1, MEF2C and BDNF genes with BMD in women of Northern México. Materials and methods: This study involved 124 unrelated Mexican women between 40 and 80 years old. BMD was determined by dual X-ray absorptiometry. Genotyping was performed using allelic discrimination by real time PCR. We analyzed the SNP of JAG1 (rs6514116, rs2273061, rs2235811 and rs6040061), MEF2C (rs1366594, rs12521522 and rs11951031), and BDNF (rs6265) and the data using linear regression. Results: The JAG1 SNP rs2235811 was associated with the BMD of the total body under the dominant inheritance model (p=0,024). Although the other SNPs were not associated with BMD in any of the inheritance models studied, a trend was observed. Conclusion: Our results suggest that the SNP rs2235811 in the JAG1 gene might contribute to the variation in BMD in women from northern México.